Features of gut microbiota and short-chain fatty acids in patients with first-episode depression and their relationship with the clinical symptoms - Yu, Shuhan; Wang, Lan; Jing, Xinyang; Wang, Yujing; An, Cuixia (Frontiers in Psychology, 2023)
Objective: To compare the differences in gut microbiota and short-chain fatty acids (SCFAs; metabolites of gut microbiota) in the serum of patients with first-episode depression and the healthy population and to analyze the relationship between gut microbiota and metabolite SCFAs and the clinical symptoms of major depressive disorder (MDD). Methods: A total of 45 patients with first-episode depression and 22 healthy volunteers were chosen to complete relevant scale evaluations, and feces samples and venous blood samples were collected. The 16SRNA method was used to analyze the intestinal microflora and the characteristics of serum SCFAs detection by ELISA kit, as well as the intestinal flora, SCFAs content and their correlation with MDD clinical indicators. Results: The abundance of Akkermansia, Megamonas, Prevotellaceae NK3B31 group, and butyrate-producing bacteria, Lachnospira, Subdoligranulum, Blautia, and Dialister, and acetate-producing bacteria, Streptococcus, in the gut microbiota of the MDD group was lower than that in the control (C) group. The abundance of Parasutterella in the MDD group was higher than that in the C group. Dialister negatively correlated with all measured clinical symptoms (r < 0, P < 0.05). The serum SCFA content in the MDD group was higher than that in the C group, and the content positively correlated with the Hamilton anxiety scale scores (r = 0.584, P < 0.05). Conclusions: The results demonstrated that the MDD group differed from the C group in terms of gut microbiota and SCFAs in the serum and that the change in certain intestinal bacteria might participate in the pathogenic mechanism of MDD.